Effect of Liquidity, Profitability, Asset Structure, Company Size, Sales Growth, and Business Risk on Capital Structure - Nadya Ihda Nastiti; Moch. Irsad (Entrepreneurship Faculty, Universitas Garut, 2022)
This study aims to examine the effect of liquidity, profitability, asset structure, firm size, sales growth, and business risk on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. This sampling technique was carried out using a purposive sampling method, with an observation period from 2015 to 2019, so that 187 observation data were obtained. The secondary data source in this study came from the Indonesia Stock Exchange. The data analysis technique used multiple regression analysis using the SPSS program. Based on the analysis results can be Key: (1) Liquidity, Profitability, and Asset Structure have a significant negative effect on capital structure; (2) sales growth has a significant positive effect on capital structure; (3) Company Size and Business Risk have no significant effect on capital structure. Dalam penelitian ini bertujuan untuk menguji pengaruh likuiditas, profitabilitas, sturuktur aktiva, ukuran perusahaan, pertumbuhan penjualan, dan risiko bisnis terhadap struktur modal pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia tahun 2015-2019. Teknik pengambilan sampel ini dilakukan dengan metode purposive sampling, dengan periode pengamatan selama tahun 2015 sampai 2019, sehingga didapatkan data observasi sebanyak 187. Sumber data sekunder dalam penelitian ini berasal dari Bursa Efek Indonesia. Teknik analisis data menggunakan analisis regresi berganda dengan menggunakan program SPSS. Berdasarkan hasil analisis dapat disimpulkan: (1) Likuiditas, Profitabilitas, dan Struktur Aktiva berpengaruh negatif signifikan terhadap struktur modal; (2) Pertumbuhan Penjualan berpengaruh positif signifikan terhadap struktur modal; (3) Ukuran Perusahaan dan Risiko Bisnis tidak berpengaruh signifikan terhadap struktur modal.